Reversal from endothermic to exothermic behavior of imidazolium-based ionic liquids in molecular solvents - Rai, Gitanjali; Kumar, Anil (Chemical Physics Letters, 2010)
In this communication, we present an interesting reversal in the enthalpic behavior from endothermic to exothermic on increasing the carbon chain length attached to the imidazolium ring in the imidazolium-based ionic liquids. A systematic investigation is presented on the excess partial molar enthalpy, H(IL)(E) directly measured using isothermal titration calorimeter at 298.15 K for the interactions operating between cation and anion of four imidazolium ionic liquids with aqueous and various non-aqueous solvents. This reversal behavior is analyzed in terms of hydrophobic and solvation effects. (C) 2010 Published by Elsevier B.V.

Enthalpic approach to delineate the interactions of cations of imidazolium-based ionic liquids with molecular solvents - Rai, Gitanjali; Kumar, Anil (Physical Chemistry Chemical Physics, 2011)
We present a systematic investigation on the enthalpic assessment of the interactions operating between the cation and anion of four imidazolium ionic liquids with aqueous and various nonaqueous solvents. Accurate experimental information gathered with the help of an isothermal titration calorimeter at 298.15 K has been analyzed for excess partial molar enthalpy of the ionic liquid, H(IL)(E), in terms of hydrophobic and solvation effects. The variations in the limiting excess partial molar enthalpy of the ionic liquid, H(IL)(E infinity), have been correlated with solvent properties. We have quantified the enthalpic effects due to dissociation of ionic liquids in very dilute solutions and to clathrate formation with the increasing concentration of ionic liquid. A change in enthalpic behavior from endothermic to exothermic is observed on increasing the carbon chain length attached to the imidazolium ring. The solvent reorganization around the cationic species has been unraveled by employing the ionic liquid interaction parameters called as H(IL-IL)(E) deduced from the H(IL)(E) data. The apparent relative molar enthalpy, phi(L), derived from H(IL)(E) data has been examined in the light of the specific ion interaction theory as advanced by Pitzer with accurate results.

Probing thermal interactions of ionic liquids with dimethyl sulfoxide - Rai, Gitanjali; Kumar, Anil (Chemphyschem, 2012)
Interactions between ionic liquids and dimethyl sulfoxide (DMSO) are probed by isothermal titration calorimetry. The excess partial molar enthalpies of ionic liquids H-IL(E) in DMSO are discussed in terms of solutesolvent interactions. The specific interaction theory originally developed by Pitzer is used to analyze the apparent molar enthalpy phi(L) of ionic liquids in DMSO with the help of ion-interaction parameters. Furthermore, quantitative information on solvent reorganization and clathrate formation is obtained and interpreted.
Keywords: calorimetry; dimethyl sulfoxide; ionic liquids; solvent effects; thermochemistry

Interesting thermal variations owing to cationic ring structural features in protic ionic liquids - Rai, Gitanjali; Kumar, Anil (Physical Chemistry Chemical Physics, 2013)
The present communication divulges interesting thermal behavior of different protic ionic liquids arising due to the hydrophobicity modifications in their parent cationic ring structures. This work assists us in differentiating between protic ionic liquids, their aprotic counterparts and common electrolytes in water. The thermal signatures produced by protic ionic liquids, aprotic ionic liquids and electrolytes emerge as individual fingerprints for them.

Calorimetric elucidation of ionic interactions in room temperature ionic liquid solutions - Rai, Gitanjali; Kumar, Anil (Clean Technologies and Environmental Policy, 2014)
Knowledge of thermal properties of room temperature ionic liquid (RTIL) solutions is essential in chemical process designing in addition to their application in understanding ionic interactions at molecular level. RTILs are considered to be substitutes for volatile organic compounds. While some experimental thermal data on these systems are available in a random manner, the modeling efforts to correlate enthalpy-concentration profiles of RTIL solutions are very scanty. In this review, an effort has been made to compare and discuss the experimental data of these RTIL solutions available in the literature. The readers are also made aware of the disappointing situation regarding the availability of any type of correlative models for the enthalpy-concentration data of the RTIL systems. An accurate knowledge of activity coefficients at infinite dilutions, Iyen (i) (a) acquired from thermal data will serve as inputs for the newer less polluting process designing and thus open opportunity for a cleaner environment.
Keywords: Calorimeters; Correlative models; Excess partial molar enthalpy; Room temperature ionic liquids

Elucidation of ionic interactions in the protic ionic liquid solutions by isothermal titration calorimetry - Rai, Gitanjali; Kumar, Anil (Journal of Physical Chemistry B, 2014)
The strong hydrogen-bonded network noted in protic ionic liquids (PILs) may lead to stronger interactions of the ionic entities of PILs with solvents (water, methanol, ethylene glycol, climethylsulfoxide (DMSO), N,N'-dimethylformamide (DMF)) as compared with those of aprotic ionic liquids (APILs). The PILs used in this work are 1-methylimidazolium tetrafluoroborate, 2-methylpyridinium tetrafluoroborate, and N-methylpyrrolodinium tetrafluoroborate in comparison to 1-butyl-3-methylimidazolium tetrafluoroborate, which is classified as an APIL. In this work, the excess partial molar enthalpy, H-IL(E) obtained from isothermal calorimetric titrations at 298.15 K is used to probe the nature of interactions of the PIL cations with solvent molecules against those present in APIL solvent systems. This work also reports interesting flip-flopping in the thermal behavior of these PIL-solvent systems depending upon the structure of the cationic ring of a PIL. In some cases, these flip-flops are the specific fingerprints for specific PILs in a common solvent environment. The excess partial molar enthalpy at infinite dilution, H-IL(E,infinity), of these PILs bears a critical dependence on the solvent properties. An analysis of relative apparent molar enthalpies, phi(L), of the PIL solutions by the ion interaction model of Pitzer yields important information on ionic interactions of these systems.

Interesting viscosity changes in the aqueous urea-ionic liquid system: effect of alkyl chain length attached to the cationic ring of an ionic liquid - Nanda, Raju; Rai, Gitanjali; Kumar, Anil (Journal of Solution Chemistry, 2015)
In the present article, we demonstrate the effect of urea on the structure of the ionic liquids in their aqueous solutions through viscometric methods. We unravel the structure altering effect of urea in its aqueous solutions of ionic liquids possessing higher alkyl chains. The finding is an attempt to discern the anomalous behavior of urea as shown in the past with the help of many techniques. Interestingly, in the aqueous solutions of the imidazolium based ionic liquids having substitution of -C4H9 and -C6H13 groups on the imidazolium ring, urea exhibits kosmotropic behavior. Further increase in the substituted alkyl group such as -C8H17 alters the urea behavior to be chaotropic.
Keywords: Alkyl chain length; ionic liquids; Structure-breaker; Structure-maker; Urea; viscosity

Isothermal titration calorimetric study of the ionic liquid solutions in alcohols in extreme dilutions: an investigation of ion-solvent interactions - Rai, Gitanjali; Jain, Preeti; Kumar, Anil (Journal of Solution Chemistry, 2016)
In this work an effort has been made to show the effect of an alcohol-rich environment on imidazolium-based ionic liquids at 298.15 K using an isothermal titration calorimeter. It is divulged from this study that the thermal behavior expressed in terms of excess partial molar enthalpy, \( H_{\text{IL}}^{\text{E}} \), of ionic liquids in various linear alcohols is governed by the increasing hydrophobicity of the residual alkyl group attached to the cation of an ionic liquid and to the alcohol molecules. An interesting observation about the systems consisting of ethylated residuals on both the cations of the ionic liquid and the alcohol molecules is that these systems do not follow the trend exhibited by other ionic liquid–alcohol systems. Interesting information on ionic interactions is obtained by using a simple methodology that gives the enthalpic interaction parameter \( H_{{I{\text{L - IL}}}}^{\text{E}} \).
Keywords: Ionic liquidsAlcoholsExcess enthalpyIsothermal titration calorimeter